PERHITUNGAN PEMBUATAN EMAS-192, IRIDIUM-192 DAN LUTESIUM-177 DENGAN AKTIVASI NEUTRON UNTUK PARTIKEL NANO RADIOAKTIF - Awaludin, Rohadi (Jurnal Radioisotop dan Radiofarmaka, 2008)
CALCULATION OF PRODUCTION OF GOLD-198, IRRIDIUM-192 ANDLUTETIUM-177 BY NEUTRON ACTIVATION FOR RADIOACTIVE NANOPARTICLE. It was reported that nanoparticle was effective for cancer treatment by thermotherapy. It is also possible to kill cancer cell by radiation of radioisotope from nanoparticle. A study on production ofradioactive nanoparticles by neutron activation has been carried out. Nanoparticles of gold, iridium and lutetium with diameter of 100 nm were studied. Calculations were carried out for irradiation at central irradiation position (CIP) of GA siwabessy reactor for 12 days. Calculation results showed that gold-198 with radioactivity of 0.378 Bq was produced in the gold nanoparticle. In the irridium nanoparticle, 192Irwith radioactivity of 0.179 Bq was produced. Radioisotope of 194Irwas also produced with radioactivity 0.337Bq at the end of irradiation in the iridium nanoparticle. The radioisotop decayed fast and became 0.000133Bq after 10 days. In the lutetium nanoparticle, I77Lu with radioactivity of 0.0884Bq was produced. In the lutetium nanoparticle, 176mLuand 177mLuwerealso produced. Lutetium-176m decayed fast and I77Lu radioactivity was 0.0095% of the I77Lu radioactivity at the end of irradiation. During neutron irradiation, the nanoparticle was put in the quartz ampule and aluminum capsules. Radioisotopes with short half life were produced in thequartz and aluminum.Keywords: gold-198, iridium-l92, lutetium-l77, neutron activation27